Spontaneous Giving under Structural Inequality: Intuition Promotes Cooperation in Asymmetric Social Dilemmas - Lotz, Sebastian (PLoS One, 2015)
The present research investigates the role of intuitive mental processing on cooperation in experimental games involving structural inequality. Results from an experiment using conceptual priming to induce intuitive mental processing provide the first evidence that cooperation is promoted by intuition in an asymmetric context that distributes the gains from cooperation unequally among a group. Therefore, the results extend our understanding of the cognitive underpinnings of human cooperation by demonstrating the robustness of intuitive cooperation in games involving structural inequality regarding asymmetric gains from cooperation. Additionally, the results provide the first successful conceptual replication of the intuition-cooperation link using conceptual priming, therefore also contributing to the debate about the validity of previous research in other contexts. Taken together, the present research contributes to the literature on psychological and institutional mechanisms that promote cooperation.